Entre instrumentalisation et autonomisation - Pascal Bianchini (Cahiers de la Recherche sur l'Education et les Savoirs)
In sub-saharan Africa, press history and social movements stemming from teaching crisis history show a high level of interdependence. Newspapers can be seen as a mirror of the different social mobilisation around school and university stakes, through more or less elaborated strategies of censorship and disclosure. But the development of new kinds of press is partly due to the these social movements which protest against ruling class hegemony. Nevertheless, the “communicationnal configuration” which results from it isn’t univocal: Senegal situation enable to see the first states of autonomous “journalistic field” constitution, whe-reas in Burkina Faso, this institutional dynamic has been disturbed by the strong social and political polarisation.